Rezolvati ecuatiile :
a) -13x+4 = 21 +4x
b) 0,3x - 0,6 = 0,1x + 0,8
c) (4x-3) · (-3) = 6x +23
d) 5(x-3) +11 = 2x
e) 6(x+2) - 8 = 3x + 14
f) 5(x-0,4) = 17 - 2x
g) 44-13x = 100 - 2(8x-5)
Răspunsuri la întrebare
Răspuns de
62
a) -13x+4 = 21 +4x
-13x-4x=21-4
-17x=17 inmultim-1
x=-17/17
x=-1
b) 0,3x - 0,6 = 0,1x + 0,8
0,3x-0,1x=0,8+0,6
0,2x=1,4
x=1,4/0,2
x=7
c) (4x-3) · (-3) = 6x +23
-12x+9=6x+23
-12x-6x=23-9
-18x=14 ·-1
x=14/18=7/9
d) 5(x-3) +11 = 2x
5x-15+11=2x
5x-2x=4
3x=4
x=4/3
e) 6(x+2) - 8 = 3x + 14
6x+12-8=3x+14
6x-3x=14-4
3x=10
x=10/3
f) 5(x-0,4) = 17 - 2x
5x-2=17-2x
5x+2x=17+2
7x=19
x=19/7
g) 44-13x = 100 - 2(8x-5)
44-13x=100-16x+10
-13x+16x=90-44
3x=46
x=46/3
-13x-4x=21-4
-17x=17 inmultim-1
x=-17/17
x=-1
b) 0,3x - 0,6 = 0,1x + 0,8
0,3x-0,1x=0,8+0,6
0,2x=1,4
x=1,4/0,2
x=7
c) (4x-3) · (-3) = 6x +23
-12x+9=6x+23
-12x-6x=23-9
-18x=14 ·-1
x=14/18=7/9
d) 5(x-3) +11 = 2x
5x-15+11=2x
5x-2x=4
3x=4
x=4/3
e) 6(x+2) - 8 = 3x + 14
6x+12-8=3x+14
6x-3x=14-4
3x=10
x=10/3
f) 5(x-0,4) = 17 - 2x
5x-2=17-2x
5x+2x=17+2
7x=19
x=19/7
g) 44-13x = 100 - 2(8x-5)
44-13x=100-16x+10
-13x+16x=90-44
3x=46
x=46/3
Răspuns de
10
a)-9x=-17
x=-9/17
b)3/10x-6/10=1/10x+8/10
Inmultim cu 10 ca sa scapam de numitor
3x-6=x+8
2x=14
x=7
c) -12x--9=6x+23
-6x=14
x=-14/6=-7/3
d)5x-15+11=3x
5x-3x-15=11
2x=26
x=13
e)6x+12-8=3x+14
6x+4=3x+14
9x=18
x=2
f) 5x-2=17-2x
7x=15
x=15/7
g) 44-13x=100-16x-10
-3x-44=110
-3x=154
x=-154/3
adelinaade36:
ce inseamna / ?
Alte întrebări interesante
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă
Biologie,
9 ani în urmă
Informatică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă